Teaching methods for senior learning courses in Taiwan: the importance of motivation, interaction, and integration. Issue 1 (2nd January 2023) - Yeh, Chun-Ting
ABSTRACT: Since 2008, the Taiwanese government has been establishing Active Aging Learning Centers (AALCs) throughout Taiwan. As of 2021, AALCs had been established in Taiwan's 368 townships and cities, representing a milestone in the development of senior education in Taiwan. This study investigated the experiences of AALC lecturers with various teaching methods and analyzed the importance of these methods. Semistructured interviews were conducted with 24 selected lecturers (8 men and 16 women aged 28–71 years). The results revealed the following: (1) Emphasizing the comprehensiveness of a course and the professional qualifications it provides at the beginning of that course can motivate learners to learn. (2) The lecturers adopted four teaching techniques: understanding differences, keen observation, interactive teaching, and teaching demonstration. These techniques had different implementation principles and levels of importance in lecture- and practical courses. (3) Teaching methods centered on older adults should satisfy the psychological and self-esteem needs of older learners and help them acquire knowledge and master skills; as such, teachers should simultaneously exhibit warmth and impart knowledge. (4) The integration of and reflection on teaching practices facilitated the integration of teaching content with teachers' expertise and experience and highlighted the importance of senior learning.